PENGARUH KEGIATAN KELOMPOK KERJA GURU (KKG) DAN MOTIVASI KERJA TERHADAP INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DI WILAYAH II KABUPATEN REJANG LEBONG - Sangkan Hidayat Darmawan (UIN Fatmawati Sukarno Bengkulu, 2018)
The arm of the study where (1) To investigate wheter or not there was a significant influence between KKG PAI at elementary school toward learning inovation in area II Rejang Lebong Regency. (2) To investigate wheter or not there was a significant influence between work motivation toward learning inovation in area II Rejang Lebong regency. (3) To investigate wheter or not there was a significant influence of KKG and Work motivation toward religion in area II Rejang Lebong Regency. Mhetod use in this study was descriptive quantitative by applying field research 42 religion teachers at elementary school in area II Rejang Lebong were the population. Simple linier regresion and doubel liniear regresion were used as the technique of data analisys by aplying SPSS version 16.0 the finding revealed that the contribution of teachers work group (KKG) toward religion inovation wa 27,2 % and the contribution of religion work motivation was 0,96%. The contribution between teachers work group (KKG) (X1) and work motivation (X2) gave positive and significant influence toward learning inovation (Y) in area II Rejang Lebong regency as equal 25,4 % in conclusion there were significant influence between teachers work group and work motivation toward learning inovation at elementary school religion in area II Rejang Lebong Regency